Efficacy and safety of gene therapy with onasemnogene abeparvovec in children with spinal muscular atrophy in the D-A-CH-region: a population-based observational studyResearch in context - Claudia Weiß; Lena-Luise Becker; Johannes Friese; Astrid Blaschek; Andreas Hahn; Sabine Illsinger; Oliver Schwartz; Günther Bernert; Maja von der Hagen; Ralf A. Husain; Klaus Goldhahn; Janbernd Kirschner; et al. (Elsevier, 2024)
Summary: Background: Real-world data on gene addition therapy (GAT) with onasemnogene abeparvovec (OA), including all age groups and with or without symptoms of the disease before treatment are needed to provide families with evidence-based advice and realistic therapeutic goals. Aim of this study is therefore a population-based analysis of all patients with SMA treated with OA across Germany, Austria and Switzerland (D-A-CH). Methods: This observational study included individuals with Spinal Muscular Atrophy (SMA) treated with OA in 29 specialized neuromuscular centers in the D-A-CH-region. A standardized data set including WHO gross motor milestones, SMA validated motor assessments, need for nutritional and respiratory support, and adverse events was collected using the SMArtCARE registry and the Swiss-Reg-NMD. Outcome data were analyzed using a prespecified statistical analysis plan including potential predictors such as age at GAT, SMN2 copy number, past treatment, and symptom status. Findings: 343 individuals with SMA (46% male, 54% female) with a mean age at OA of 14.0 months (range 0-90, IQR 20.0 months) were included in the analysis. 79 (23%) patients were clinically presymptomatic at the time of treatment. 172 (50%) patients received SMN2 splice-modifying drugs prior to GAT (risdiplam: n = 16, nusinersen: n = 154, both: n = 2). Functional motor improvement correlated with lower age at GAT, with the best motor outcome in those younger than 6 weeks, carrying 3 SMN2 copies, and being clinically presymptomatic at time of treatment. The likelihood of requiring ventilation or nutritional support showed a significantly increase with older age at the time of GAT and remained stable thereafter. Pre-treatment had no effect on disease trajectories. Liver-related adverse events occurred significantly less frequently up to 8 months of age. All other adverse events showed an even distribution across all age and weight groups. Interpretation: Overall, motor, respiratory, and nutritional outcome were dependent on timing of GAT and initial symptom status. It was best in presymptomatic children treated within the first six weeks of life, but functional motor scores also increased significantly after treatment in all age groups up to 24 months. Additionally, OA was best tolerated when administered at a young age. Our study therefore highlights the need for SMA newborn screening and immediate treatment to achieve the best possible benefit-risk ratio. Funding: The SMArtCARE and Swiss-Reg-NMD registries are funded by different sources (see acknowledgements).